Novel SNPs in heat shock protein 70 gene and their association with sperm quality traits of Boer goats and Boer crosses - Nikbin, Saeid; Panandam, Jothi Malar; Yaakub, Halimatun; Marimuthu, Murugaiyah; Sazili, Awis Qurni (Elsevier, 2014)
The semen quality of bucks affects the reproduction performance of the herd and is influenced by genetic and non-genetic factors. Heat shock protein 70 (HSP70) is considered as an important gene affecting semen quality traits. The objectives of this study are to find single nucleotide polymorphisms in HSP70 coding region and their association with semen quality traits on Boer and Boer cross bucks. DNA isolated from 53 goats (36 pure South African Boer and 17 Boer crosses) was subjected to PCR amplification of the exon 1 region of the caprine HSP70 gene. Single-strand conformation polymorphism (SSCP) was used to detect polymorphisms and the variant DNA fragments were sequenced. Two synonymous SNPs (74A > C (ss836187517) and 191C > G (ss836187518)) were detected. Qualities of fresh and post-thaw semen were evaluated for sperm concentration, semen volume, sperm motility and velocity traits, live sperm percentage, and abnormal sperm rate. The C allele of ss836187517 and G allele of ss836187518 were at higher frequencies in both the breeds. The C allele of ss836187517 appeared to be the favorable allele for semen concentration, progressive motility of fresh semen, and motility and sperm lateral head displacement of post-thaw semen. A negative overdominance was observed for ss836187517 alleles on velocity traits of post-thaw semen. The C allele of ss836187518 was favorable for sperm concentration and progressive motility. Results herein suggest that the SNPs in HSP70 may affect on semen quality in tropical regions and specially on the potential of semen for freezing.